Mercury exposure in ringed seals (Pusa hispida saimensis) in Lake Saimaa, Finland, and the placenta as a possible non-invasive biomonitoring tool - Simola, Jesse; Kunnasranta, Mervi; Niemi, Marja; Biard, Vincent; Akkanen, Jarkko (Environmental Science and Pollution Research)
The Saimaa ringed seal (Pusa hispida saimensis) is a subspecies of ringed seal, landlocked in Lake Saimaa, Finland. The small population of less than 500 seals is facing many human-induced threats, including chemical contaminants. Mercury, in particular, has previously been suggested to be one of the chemicals affecting the viability of this endangered population. We analysed mercury concentrations from placentas and lanugo pup tissues (blubber, brain, kidney, liver, and muscle) to determine current prenatal exposure levels. These pups were found dead in or near birth lairs and were less than 3 months old. Additionally, we used threshold values available in the literature to estimate the potential mercury toxicity to the Saimaa ringed seal. We also determined selenium concentrations for its potential to alleviate the adverse effects of mercury. We further supplemented our study with brain samples collected from various seal age classes. These seals were found dead by either natural causes or by being caught in gillnets. The analysed chemicals were present in all tissues. For lanugo pups, mercury concentrations were the highest in the kidney and liver, whereas the highest selenium to mercury molar ratio was observed in placentas. The toxicity evaluation suggested that, in severe cases, mercury may cause adverse effects in lanugo and older pups. In these cases, the selenium concentrations were low and selenium to mercury ratio was below 1:1 threshold ratio and thus unlikely to provide adequate protection from the adverse effects of mercury. Furthermore, adverse effects are more likely to occur in adult seals, as mercury bioaccumulates, leading to higher concentrations in older individuals. Placental mercury concentrations correlated to those in the livers and muscle tissues of lanugo pups. This, together with the fact that placentas can be collected non-invasively and in good condition, provides a potential novel method for biomonitoring mercury exposure in Saimaa ringed seals. 2024